2007
DOI: 10.1007/s11270-007-9505-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Water and Sediments Pollution of An Arid Saltern (Sfax, Tunisia) by Coupling the Distribution of Microorganisms With Hydrocarbons

Abstract: International audienceWe investigated the coupling of abundance of bacteria, phytoplankton and ciliates with hydrocarbons in the surface water and sediments of five interconnected ponds in the arid Sfax solar salterns. This study aimed at determining the potential sources of hydrocarbons and the effects of salinity gradients on microorganism metabolism. Hydrocarbon analysis was performed by gas chromatography (GC-FID) and gas chromatography coupled with mass spectrometry (GC-MS). The GC-FID allowed the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…The high salt concentration found in water samples throughout the study is the clearest evidence of the Sabkha El Meleh influence on the Karboub ecosystem (Kchaou et al, 2009). This is reflected by the presence of substantial amounts of halotolerant Hetrotrichea F. salina (9.2 % of the ciliate total abundance), in Karboub samples, a species that was also found in high abundance in the primary ponds of Sfax saltern (Elloumi et al, 2008), yet in higher salinities (range . This change in ambient salinity resulted in smaller F. salina at the Karboub station (length = 75 µm; biovolume = 44.3 µm 3 ) than in the Sfax saltern (length = 111 µm; biovolume = 108.1 µm 3 ) (Elloumi et al, 2006(Elloumi et al, , 2009b.…”
Section: Composition Of the Ciliate Communitymentioning
confidence: 82%
See 1 more Smart Citation
“…The high salt concentration found in water samples throughout the study is the clearest evidence of the Sabkha El Meleh influence on the Karboub ecosystem (Kchaou et al, 2009). This is reflected by the presence of substantial amounts of halotolerant Hetrotrichea F. salina (9.2 % of the ciliate total abundance), in Karboub samples, a species that was also found in high abundance in the primary ponds of Sfax saltern (Elloumi et al, 2008), yet in higher salinities (range . This change in ambient salinity resulted in smaller F. salina at the Karboub station (length = 75 µm; biovolume = 44.3 µm 3 ) than in the Sfax saltern (length = 111 µm; biovolume = 108.1 µm 3 ) (Elloumi et al, 2006(Elloumi et al, , 2009b.…”
Section: Composition Of the Ciliate Communitymentioning
confidence: 82%
“…The seasonal distribution of the ciliate community, coupled with environmental factors along the coast of the Gulf of Gabes, is investigated at three sampling stations (Tabia, Karboub and the Port of Gabes) (Kchaou et al, 2009). However, data on large scale distribution of ciliate assemblages are lacking, except, for a study on a man-made solar saltern receiving water inputs from the Gulf of Gabes (Elloumi et al, 2006(Elloumi et al, , 2008(Elloumi et al, , 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their considerable landscape and economic value, and though studies clearly indicate that the salt-production process via evaporation and precipitation is closely related to biological processes (Davis 1990(Davis , 2000, salterns are now threatened biotopes, mainly due to human interference. This is particularly true of the Sfax saltern located on the southwestern Mediterranean coast and which suffered from pollution by phosphogypsum (Rekik et al 2012) and petroleum products (Elloumi et al 2008). Indeed, the anthropogenic nutrient input in the saltern'sre ce iving pond may have impacted the development of the ponds biological communities and correlatively the quality of the salt produced (1990).…”
Section: Introductionmentioning
confidence: 99%
“…This method involves the removal of oxygen-deficient water from the lake's hypolimnion layer, which is characterized by significant fertility and the presence of methane, hydrogen sulphide and decomposable organic matter, to the receiving body, usually a river (Cooke et al, 1982;Klapper, 1991;Nürnberg, 2007;Górniak et al, 2014;Zamparas and Zacharias, 2014). Hypolimnion water pollutes the watercourse into which it is discharged, and it induces periodic changes in hydrochemical and biological conditions (Elloumi et al, 2008). Some previous studied showed that without careful management, hypolimnetic releases can degrade water quality in the receivers such as rivers with small flows (Marshall et al, 2006;Nürnberg, 2007).…”
Section: Introductionmentioning
confidence: 99%